2020
DOI: 10.1029/2020gl088303
|View full text |Cite
|
Sign up to set email alerts
|

Strong Sequestration of Hydrogen Into the Earth's Core During Planetary Differentiation

Abstract: We explore the partitioning behavior of hydrogen between coexisting metal and silicate melts at conditions of the magma ocean and the current core–mantle boundary with the help of density functional theory molecular dynamics. We perform simulations with the two‐phase and thermodynamic integration methods. We find that hydrogen is weakly siderophile at low pressure (20 GPa and 2,500 K), and becomes much more strongly so with pressure, suggesting that hydrogen is transported to the core in a significant amount d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 87 publications
(128 reference statements)
5
35
0
Order By: Relevance
“…often reported as water) and determined the H-content in the silicate melts, but so far, only three studies measured the partitioning of H between metal and silicate melts (Okuchi, 1996;Clesi et al, 2018;Malavergne et al, 2019) to 21 GPa, and recently, Tagawa et al (2021) indirectly estimated D H at 30-60 GPa 3100-4600 K (using the phase proportions and the cell volume of FeHx et -FeOOH to get the H content in metals). These studies reported significant effects of P, T and fO2 on H metalsilicate partitioning that are consistent with molecular dynamics calculations at extreme P and T (Zhang and Yin, 2012;Li et al 2020, Yuan andSteinle-Neumann, 2020). Finally, empirical relationships have also been established to predict the molten metalsilicate liquid partitioning of H (Clesi et al, 2018;Malavergne et al, 2019;Tagawa et al 2021).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…often reported as water) and determined the H-content in the silicate melts, but so far, only three studies measured the partitioning of H between metal and silicate melts (Okuchi, 1996;Clesi et al, 2018;Malavergne et al, 2019) to 21 GPa, and recently, Tagawa et al (2021) indirectly estimated D H at 30-60 GPa 3100-4600 K (using the phase proportions and the cell volume of FeHx et -FeOOH to get the H content in metals). These studies reported significant effects of P, T and fO2 on H metalsilicate partitioning that are consistent with molecular dynamics calculations at extreme P and T (Zhang and Yin, 2012;Li et al 2020, Yuan andSteinle-Neumann, 2020). Finally, empirical relationships have also been established to predict the molten metalsilicate liquid partitioning of H (Clesi et al, 2018;Malavergne et al, 2019;Tagawa et al 2021).…”
Section: Introductionsupporting
confidence: 72%
“…(2020) and Yuan and Steinle-Neumann (2020) conducted on C-free systems that reported increasing P makes H sensibly more siderophile. At ca.…”
Section: 3h-speciation and Partitioning In P-t-fo2 Spacementioning
confidence: 99%
“…However, these possibilities are less likely. The water content of the core remains controversial (e.g., Clesi et al., 2018; Hirose et al., 2019; Iizuka‐Oku et al., 2017; Li et al., 2020; Okuchi et al., 1997; Terasaki et al., 2012; Yuan & Steinle‐Neumann, 2020), but it is most likely not decreasing over time, making it an unlikely source of an increase in mantle water. Possible hydrous partial melts in the early mantle would have likely been too buoyant to remain gravitationally stable at depth (Mookherjee et al., 2008) and would have erupted to release their water onto the surface.…”
Section: Resultsmentioning
confidence: 99%
“…If O is an additional impurity element in the outer core (note that O is not soluble into the inner core and thus does not alter the possible range of the inner core composition considered here) and TICB = 6000 K, the outer core liquid may include 1.7-4.4 wt% O 52 along with 3.5 wt% Si and 0.04-0.32 wt% H (Fe60Si4.4-4.5O3.8-9.9H1. [5][6][7][8][9][10][11][12]. When TICB is 5500 K, we found liquid Fe + 3.5 wt% Si + 0.61 wt% H + 0.15 wt% O (Fe60Si4.3O0.3H21) for the outer core.…”
Section: Discussionmentioning
confidence: 76%
“…Recent planet formation theories suggested that a large amount of water could have been delivered to the growing Earth [3][4][5] . The chemical reaction of water with Fe metals in a magma ocean led to the incorporation of hydrogen (H) along with silicon (Si) and oxygen (O) into the core [6][7][8][9] . While O is least partitioned into solid Fe and should therefore be negligible in the inner core [10][11][12] , both Si and H are likely to be present in both the outer and inner core.…”
Section: Introductionmentioning
confidence: 99%